2023
DOI: 10.1186/s12870-023-04282-z
|View full text |Cite|
|
Sign up to set email alerts
|

Diversity and correlation analysis of endophytes and metabolites of Panax quinquefolius L. in various tissues

Abstract: Background Panax quinquefolius L. (American ginseng) is widely used in medicine due to its wealth of diverse pharmacological effects. Endophytes colonize within P. quinquefolius in multiple tissue types. However, the relationship between endophytes and the production of their active ingredients in different parts of the plant is not clear. Results In this study, the relationship of endophytic diversity and the metabolites produced in different plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…The results show that the HL sampling area had the highest number of endophytic bacterial OTUs in the root of B. vivipara , which accounted for 38.44%, whereas the GQ sampling area had the lowest number of endophytic bacterial OTUs in the root of B. vivipara , which accounted for 3.22% ( Figure 4 ). The number of endophytic bacterial OTUs shared by the B. vivipara roots, which were collected from five different sampling areas, was extremely low, ranging from 0% to 1.47%, indicating that the composition of endophytic bacteria in B. vivipara roots, collected from different sampling areas, may be significantly different ( Figure 4 ) [ 19 ]. The diversity and abundance of endophytic bacteria in the roots of B. vivipara , which were collected from different sampling areas, were analyzed using Chao1, Simpson, and Shannon indices ( Figure 5 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results show that the HL sampling area had the highest number of endophytic bacterial OTUs in the root of B. vivipara , which accounted for 38.44%, whereas the GQ sampling area had the lowest number of endophytic bacterial OTUs in the root of B. vivipara , which accounted for 3.22% ( Figure 4 ). The number of endophytic bacterial OTUs shared by the B. vivipara roots, which were collected from five different sampling areas, was extremely low, ranging from 0% to 1.47%, indicating that the composition of endophytic bacteria in B. vivipara roots, collected from different sampling areas, may be significantly different ( Figure 4 ) [ 19 ]. The diversity and abundance of endophytic bacteria in the roots of B. vivipara , which were collected from different sampling areas, were analyzed using Chao1, Simpson, and Shannon indices ( Figure 5 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, many chemical constituents extracted from the tissues of the roots, stems, and leaves of host plants were shown to have important medicinal value, such as saponins, phenolic acids, etc. [ 19 , 20 ]. A study focusing on different metabolites in the root samples of B. vivipara showed that the metabolites with significant differences (and with respect to each sampling area) included many important medicinal components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Li et al (2023) highlighted Ascomycota as the dominant fungal phylum in ginseng roots. Our research expanded on this by including Basidiomycota in addition to Ascomycota.…”
Section: Discussionmentioning
confidence: 99%